Management Mode of Architecture and Artificial Intelligence (Ai) Interaction Across Design Phases Based on Generative Design - Tao Rui; Sodbhiban, Pichai (Journal of Modern Learning Development, 2024)
This research delves into the transformative intersection of Artificial Intelligence (AI) and architectural design, with a particular focus on the evolving management modes in this domain. The study is set against the backdrop of architectural landscape, a city emblematic of technological progress and cultural richness. The central aim is to unravel how AI influences and reshapes architectural practices, from the initial conceptualization stages to the final design implementation. The methodology employed is a mixed-method approach, encompassing quantitative surveys, qualitative interviews, and in-depth case studies. This comprehensive methodological framework ensures a nuanced understanding of the multifaceted nature of AI integration in architecture. The research primarily focuses on identifying and analyzing various management models (such as the 4M Management Model, Agile, Lean, and Six Sigma) and their adaptation in integrating AI within different architectural design phases. Key findings reveal a growing trend of AI adoption in architectural design, especially in the areas of generative design, which significantly enhances design efficiency, innovation, and client satisfaction. However, challenges such as resistance to technological change, data privacy concerns, and the high costs associated with AI integration also emerge as significant barriers. In conclusion, this research not only fills a critical academic gap by providing a comprehensive analysis of AI’s role in modern architectural practices but also sets the stage for future explorations in this field. It underscores the importance of balancing technological innovation with ethical and cultural considerations, paving the way for a future where architecture and AI synergistically create sustainable, efficient, and aesthetically pleasing built environments.